The Role of Form–Focused Instruction on Foreign Language Learners - Mana Alahmad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
To determine the role of form-focused instruction on foreign language learners, this study demonstrates noticing necessary in foreign language learning. In other words, an instruction through input enhancement have an effect on foreign language learning.  The participants in the study were 80 students who enrolled in Shamim Language Institute, but only 60 intermediate learners were selected by means of administering a placement test. Based on the results of the placement test, two matched groups, one as the experimental group and the other as the comparison group, were formed. So, the study utilized the experimental paradigm and tested the notion of focusing on form (FonF) as input enhancement for learning. The enhanced text, including conditional sentences as the treatment, time (pretest versus posttest), and task type (a multiple choice test and a cloze test) were used to conduct the study. The participants in control (FonM) group received the unenhanced text and discussed the topic in that session. And experimental group (FonF) concurrently received the same text enhanced and discussed it. To compare the means and the standard deviations of the pretest and the post-test tasks within the treatment, the researcher used T-Test. The results showed that type of instructional treatment led to differences in language learning in the short-term. The scores of the participants demonstrated that the experimental group outperformed the comparison group.